Leech Therapy (Jalaukavacharana): An Ancient Ayurvedic Practice and Its Modern Scientific Perspectives - Meena, Sarita; Yadav, Vijay Shanker; Maurya, Bhola Nath (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: Leech therapy, known as Jalaukavacharana in Ayurveda, is one of the oldest para-surgical procedures documented in classical Ayurvedic texts, particularly the Sushruta Samhita. This form of Raktamokshana (bloodletting) employs the medicinal leech Hirudomedicinalis and related species to treat a wide spectrum of disorders linked to vitiated blood (Raktadushti) and Pitta-Rakta imbalances. Objective: This review aims to consolidate classical Ayurvedic knowledge of leech therapy with contemporary biomedical evidence, highlighting the pharmacological properties of leech saliva, mechanisms of therapeutic action, clinical indications, contraindications, and procedural protocols. Methods: A systematic search of classical Ayurvedic texts (Sushruta Samhita, Ashtanga Hridayam, Ashtanga Sangraha, Charaka Samhita) and modern databases including PubMed, Google Scholar, Scopus, and AYUSH research portals was conducted. Articles published between 1985 and 2025 were included. Results: The saliva of medicinal leeches contains over 100 bioactive compounds including hirudin, hyaluronidase, destabilase, calin, orgelase, decorsin, and histamine-like substances. These compounds collectively exert anticoagulant, anti-inflammatory, analgesic, thrombolytic, and vasodilatory effects. Clinical evidence supports its efficacy in venous congestion, osteoarthritis, skin disorders (Kushtha), haematoma, vascular diseases, microsurgery, and multiple Pitta-Rakta disorders described in Ayurveda. Conclusion: Leech therapy represents a significant convergence of traditional Ayurvedic wisdom and modern biomedical science. Its safety, efficacy, and minimal invasiveness make it a viable integrative treatment modality. Standardisation of protocols, larger clinical trials, and pharmacological research are warranted.